2021
DOI: 10.1016/j.chest.2020.09.259
|View full text |Cite
|
Sign up to set email alerts
|

Lung Histopathology in Coronavirus Disease 2019 as Compared With Severe Acute Respiratory Sydrome and H1N1 Influenza

Abstract: Background Patients with severe Coronavirus Disease 2019 (COVID-19) have respiratory failure with hypoxemia and acute bilateral pulmonary infiltrates, consistent with acute respiratory distress syndrome (ARDS). It has been suggested that respiratory failure in COVID-19 represents a novel pathologic entity. Research Question How does the lung histopathology described in COVID-19 compare to the lung histopathology described in SARS and H1N1 influenza? Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
0
15

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(165 citation statements)
references
References 82 publications
10
140
0
15
Order By: Relevance
“…Chest CT takes a considerable part in the timely detection of lung infection abnormalities in the early phase for diagnosis of COVID-19 [ 6 ]. Also, recent studies have reported that chest CT could have higher sensitivity than RT-PCR in diagnosing COVID-19 [ 7 , 8 ]. The Fleischner Society stated that chest CT scanning is essential in diagnosing COVID-19 patients when the symptoms worsen or RT-PCR is unavailable [ 9 ].…”
Section: Introductıonmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest CT takes a considerable part in the timely detection of lung infection abnormalities in the early phase for diagnosis of COVID-19 [ 6 ]. Also, recent studies have reported that chest CT could have higher sensitivity than RT-PCR in diagnosing COVID-19 [ 7 , 8 ]. The Fleischner Society stated that chest CT scanning is essential in diagnosing COVID-19 patients when the symptoms worsen or RT-PCR is unavailable [ 9 ].…”
Section: Introductıonmentioning
confidence: 99%
“…This classification varies from very low (CO-RADS 1) to very high (CO-RADS 5). Besides, a technically inadequate examination is encoding as CO-RADS 0 and if a positive RT-PCR result was proven during the examination, it encodes as CO-RADS 6 (Table 1 ) [ 8 ].…”
Section: Introductıonmentioning
confidence: 99%
“…Lungs are recognized as the primary target organs for COVID-19 (4). However, COVID-19 patients frequently show evidence of damage to other organs.…”
Section: Introductionmentioning
confidence: 99%
“…pneumonia or aspiration) (21). Even SARS-CoV-2, a pandemic respiratory virus that causes ARDS in its most severe form, provokes both epithelial and endothelial lung injury as assessed via post-mortem examination (27,28). We believe this trend has important experimental implications, as "single-hit exposures" (such as intratracheal endotoxin in mice) are unlikely to fully recapitulate the complex pathophysiology of human ARDS.…”
Section: Discussionmentioning
confidence: 99%